Redescription of Astylus atromaculatus (Blanchard, 1843) a taxonomic contribution to the Neotropical species of the genus Astylus (Coleoptera: Melyridae) - Estrada, Patricia (Zootaxa, 2024)
Astylus atromaculatus (Blanchard, 1843), the most widely distributed taxon of the genus, is redescribed. The original description is based mainly on the coloration patterns of the elytra. The study of the external morphological characters and genitalia of the type material and from specimens of collections allows the establishment of a new synonymy between A. atromaculatus and A. atromaculatus var. duodecimmaculatus. Geographic distribution data is provided for the taxon are provided.